UPAYA MENGOLAH LIMBAH SAMPAH MENJADI PELUANG SOCIAL ENTERPRISE EKONOMI KREATIF BAGI GENERASI-Z - Hernawati W. Retno Wiratih; Ilmi Dwiastuti; Ikramina Larasati Hazrati Havidz; M Havidz Aima; Shinta Amalina Hazrati Havidz; Maya Puspita Dewi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
The problem of waste in Indonesia has reached 175,000 tons/day which is equivalent to 64 million tons/year, which until now has been managed by being transported and dumped in the final processing site (TPA) because people still have the perception that waste is a waste material that is considered useless. The COVID-19 pandemic in 2020 has limited access to activities outside the home, ultimately changing consumer behavior by shifting the way to shop for their needs to online shopping. The study method utilized social media platform to distribute the online webinar information to gathered large number of participants. Thus, the study find that the Generation Z is a generation that is synonymous with digital technology and information, as a Collaborative Generation, a generation that knows the "sharing economy" is the foundation of hope to take advantage of waste problems as challenges and opportunities that can create a generation of Social Entrepreneurs who create waste into products that have bargaining power and competitiveness in the creative economy market through social media or e-commerce platforms.